Framework of Interactive E-Assessment with Cognitive Conflict Phenomena to Measure Critical Thinking Ability: Analysis of Teachers’ Perceptions and Students’ Perspectives - Liza Okwan Admas; Fatni Mufit; Emiliannur; Fuja Novitra; Zahra Fathanah (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
The PISA 2022 results indicate that Indonesia ranked 69th out of 81 participating countries, reflecting students’ low critical thinking ability, particularly in understanding scientific concepts. This condition highlights the need for more effective and interactive learning and assessment practices. This study aims to describe a framework of an interactive electronic assessment (e-assessment) incorporating cognitive conflict phenomena based on teachers’ perceptions and students’ perspectives. The research employed a qualitative descriptive design involving 15 physics teachers and 254 senior high school students from public schools in Pesisir Selatan Regency. Data were collected using adapted questionnaires on teachers’ perceptions and students’ perspectives and analyzed using a Likert scale. The results showed that teachers’ perceptions of interactive e-assessment were categorized as very good across pedagogical aspects, facility conditions, performance expectations, behavioral intention, and social influence. Meanwhile, students’ perspectives were categorized as good, covering socio-emotional, efficiency, actual behavior, and preference aspects. Based on these findings, a framework of interactive electronic assessment based on cognitive conflict was developed and subsequently validated by four experts, with results indicating that the framework was valid. Overall, both teachers and students responded positively to the implementation of interactive e-assessment. These findings suggest that the development of cognitive conflict–based electronic assessment is essential, as it has the potential to enhance students’ critical thinking skills, learning motivation, and the overall quality of physics learning in the digital era